Motor imagery in chronic neglect: an fMRI pilot study - Simon, Joe J.; Welfringer, Anouk; Leifert-Fiebach, Gundhild; Brandt, Tobias (Journal of clinical and experimental neuropsychology, 2019)
Aim. Previous studies indicate the effectiveness of motor imagery training in stroke patients. To determine whether patients showing chronic visuospatial neglect symptoms may profit from motor imagery training, it is important to assess how the brain implements motor imagery when cortical systems involved in attentional control are impaired.Method. Therefore, in this pilot study, nine chronic neglect patients with right-hemispheric stroke performed motor imagery of a finger opposition task during functional magnetic resonance imaging (fMRI).Results. Imagery of unaffected hand movements was related to activations in the left primary somatosensory and premotor cortices as well as in the left supplementary motor area. During the imagery of the affected hand, patients displayed activations in the left premotor cortex and supplementary motor area as well as left dorsolateral prefrontal cortex. Furthermore, time since onset and visual imagery capacity were negatively related to activation in the supplementary motor area during the imagery of the affected hand.Conclusions. These initial results demonstrate motor imagery capacity in patients with chronic neglect via compensatory neural processing during motor imagery of the affected hand in ipsilateral brain regions, since we found that the supplementary motor area appears to be specifically related to neglect severity. Although our results must be treated with caution due to the small sample size and missing control group, they indicate that neglect is not necessarily an exclusion criterion for motor imagery training per se.
Published online: 06 Aug 2018
Gesehen am 16.10.2019